Delores Horne analyzing weed killer in Dow Analytical Laboratory - Dow Chemical Company (1950)
General view of chemist Delores Horne analyzing the active constituent of a weed killer in the Dow Chemical Company's Analytical Laboratory located in Midland, Michigan. Per a notation accompanying the photograph, Ms. Horne was a graduate of the University of Oklahoma. The words "Master Copy" are printed across the photograph, indicating that it was a file copy used to make reproductions for publication.
Keywords: Women in science; Weeds--Control--Research; Scientific apparatus and instruments; Dow Chemical Company; Weeds; Women chemists; Women employees; Glassware; Laboratories; Chemists; Horne, Delores